Facile fabrication of multifunctional transparent electrodes via spray deposition of indium-tin-oxide nanoparticles - Kim, Da Seul; Jung, Jae Yeong; Seo, Soonmin; Kim, Ju Hyung (Applied Surface Science, 2023)
Low-dimensional nanomaterials with various functionalities are highly promising materials for transparent electrodes which are key components of electronic and optoelectronic devices. However, conventional physical vapor deposition (PVD) methods are not applicable to low-dimensional nanomaterials because of the harsh vaporizing conditions, and using solution processing technologies as alternatives is attracting attention. Herein, we demonstrate a facile method for fabricating of multifunctional transparent electrodes via one-step spray deposition of indium-tin-oxide (ITO) nanoparticles. In this method, ITO nanoparticles are spontaneously and rapidly packed, forming electrically conductive thin films composed of random nanostructures. This method can be adapted to fabricating hierarchical structures, that is, micropatterns consisting of random nanostructures, using impermeable shadow masks. In addition, the optical and electrochemical properties of the spray-deposited ITO films were investigated to confirm their high transmission haze values and ion-storage capabilities, leading to further applications such as random scattering layers, transparent superconductors, and high-performance electrochromic devices. We expect these results to spur the development and refinement of multifunctional electrodes and their electronic and optoelectronic applications.
Keywords: Electronics devices; Facile fabrication; Indium-tin oxide nanoparticles; Ion storage; Ion-storage layer; Low dimensional; Random scattering; Spray deposition; Storage layers; Transparent electrode; Electrochromic devices; Ion-storage layers; Random scattering; Spray deposition; Transparent electrodes